Effect of Megestrol Acetate Combined With Oral Nutrition Supplement in Malnourished Lung Cancer Patients: A Single-Center Prospective Cohort Study - Duan, Baojun; Zhang, Yan; Wang, Xi; Zhang, Yulian; Hou, Yinyin; Bai, Jun; Liu, Linhua; Chen, Yaohua; Zhang, Rong; Jin, Ronghui; He, Li; Pu, Yansong (Frontiers in Nutrition, 2021)
Background: The optimal treatment of cancer-related malnutrition remains unknown. A single-center prospective cohort study was performed to compare the efficacy of megestrol acetate (MA) combined with oral nutrition supplement (ONS) and MA alone for the treatment of lung cancer-related malnutrition. Methods: 76 eligible patients were prospectively enrolled to: Arm 1 patients (n = 40, 52.6%) received MA 160 mg/d, and Arm 2 patients (n = 36, 47.4%) received MA 160 mg/d combined with ONS 55.8 g/t.i.d, all orally. All patients could receive anticancer therapy. Treatment duration was three months. The primary endpoints were improvements in body mass index (BMI) and Eastern Cooperative Oncology Group (ECOG) score. Secondary endpoints were assessed by appetite, mid-upper arm circumference (MAC), serum pre-albumin levels, and serum albumin levels. Results: Baseline levels were comparable between Arm 1 and Arm 2 patients. Compared with Arm 1, primary endpoints(BMI, P = 0.018; ECOG, P = 0.022) and secondary endpoints(MAC, P = 0.025; serum pre-albumin, P = 0.043; and serum albumin, P = 0.034) improved significantly after treatment in Arm 2. Toxicity was negligible and comparable between Arm 1 and Arm 2. Conclusion: MA combined with ONS may be an effective and safe treatment option for lung cancer-related malnutrition patients.